A Procedure for the Estimation of the Supplemental Damping for Design and Retrofit of RC Buildings with FVDs - Korkmaz, Senol; Kircil, Murat Serdar (MDPI, 2026)
Passive energy dissipation (PED) devices have been widely accepted as effective in reducing seismic effects through extensive experimental and analytical studies. However, the estimation of the supplemental damping ratio (SDR) and its relationship with seismic performance levels remain important research challenges. In this study, a supplemental damping-based procedure is proposed for the design and retrofit of reinforced concrete buildings equipped with PED systems. The proposed procedure essentially consists of two main parts, which define the overall methodological framework. The first part of the procedure is developed to establish a relationship between target seismic performance levels and SDR by explicitly considering the structure-damper interaction, rather than predetermining damping or structural parameters. The second part analytically establishes a direct relationship between the target seismic performance of the structure and the required SDR provided by fluid viscous dampers (FVDs). The results of 5808 nonlinear time history analyses indicate that the supplemental damping ratio plays a critical role in structural performance and provides significant reductions in hysteretic energy demand depending on the device characteristics, configuration, and arrangement. In addition to the key parameters of the damping system mentioned above, the proposed procedure also considers key parameters of the structural system. Furthermore, it allows these parameters to be evaluated separately with respect to seismic performance levels. Consequently, the first part of the procedure provides a detailed basis for damper optimization and realistically reveals the effects of supplemental damping on the seismic performance of new and existing reinforced concrete buildings equipped with PED systems. Furthermore, the second part offers a non-iterative and practical solution for the performance-based design and retrofit with FVDs.
Keywords: passive energy dissipation devices; supplemental damping ratio; performance-based seismic design; seismic retrofit; DISPLACEMENT-BASED DESIGN; REAL EARTHQUAKE ACCELEROGRAMS; MOMENT-RESISTING FRAMES; SEISMIC DESIGN; VISCOUS DAMPERS; STEEL FRAMES; VISCOELASTIC DAMPERS; REINFORCED-CONCRETE; RESTRAINED BRACES; FRICTION DAMPERS; Construction & Building Technology; Engineering